The Effectiveness of Structured Discharge Planning on Readiness for Discharge in Stroke Patients - Rinawati Rinawati; Wati Jumaiayah; Rohman Azzam; Dian Noviati Kurniasih (UIMA Press, 2024)
Background: Stroke is one of the non-communicable diseases (NCDs) with a continuously increasing incidence rate worldwide and in Indonesia. The implementation of discharge planning for patients in hospitals has generally not been well-executed, including providing limited education for home preparation and inadequate information related to health management. This results in ineffective discharge planning and a lack of continuity of care when the patient is at home. Objectives: This study aimed to determine the effect of structured discharge planning on home readiness in stroke patients in the hospital. Methods: This quantitative research employed a quasi-experimental design with pre- and post-test comparisons between groups. A simple random sampling technique was used, with 16 respondents in the intervention group and 16 in the control group. Data collection was conducted from April to June 2022. The Readiness for Hospital Discharge Scale (RHDS) questionnaire was used as the measuring instrument. Data analysis was carried out using a dependent t-test and an independent t-test. Results: The results indicated that structured discharge planning significantly affected the readiness to return home for stroke patients at Pasar Rebo Hospital Jakarta in both the intervention group (p-value 0.000) and the control group (p-value 0.000). Conclusion: It was concluded that there was no decrease in value from before to after the administration of structured discharge planning in both the intervention and control groups.